Aramid fiber III composite fiber and preparation method thereof
By dissolving the aminolated graphene quantum dots in N,N-dimethylacetamide solvent and adding them in the polymerization reaction, the problem of easy agglomeration in the fiber is solved, and the uniform distribution of graphene quantum dots in the fiber is achieved and fiber preparation with high mechanical properties is achieved.
Patent Information
- Application Number
- CN202311272393.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when graphene is introduced into heterocyclic aramid fibers, graphene is prone to agglomeration, resulting in uneven fibers, poor stability and poor mechanical properties, making it difficult to use in actual production.
By dissolving the aminolated graphene quantum dots in N,N-dimethylacetamide solvent, a dispersion liquid is formed and added to the polymerization reaction system before polymerization of the aramid III monomer is formed to form a composite spinning liquid to avoid graphene agglomeration.
The uniform distribution of graphene quantum dots in the fiber is achieved, and the mechanical properties of the fiber are improved, such as tensile strength, elongation of break and Young's modulus, while enhancing the corrosion resistance of the fiber.
Smart Images

Figure CN119710960A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heterocyclic aramid fibers, and more specifically to a graphene quantum dot-modified aramid III composite fiber and a preparation method thereof. Background Art
[0002] Heterocyclic aromatic polyamide fiber, referred to as heterocyclic aramid or aramid III fiber, is one of the three major high-performance fibers in the world today. Due to its excellent properties such as high strength, high modulus, impact resistance, light weight, and high temperature resistance, it has important application value in defense and military industries such as bulletproof equipment, engine housings, and aircraft skins, as well as in aerospace fields. At present, the mechanical properties of domestic aramid III fibers are still far behind those of foreign ones. It is urgent to enhance the mechanical properties of aramid III fibers and develop high-performance aramid III fiber products for different application scenarios.
[0003] Graphene is a carbon atom in the form of sp 2 The two-dimensional carbon nanomaterials with hexagonal honeycomb lattices composed of hybrid orbitals have excellent mechanical, electrical and thermal intrinsic properties and are ideal mechanical enhancers for polymer composites. Quantum dots have the characteristics of multi-color luminescence, high fluorescence quantum yield, low exciton binding energy, high carrier mobility, and wide excitation spectrum. These superior optical and electrical properties make them show great application potential in the fields of solar cells, photodetectors, light-emitting diodes and lasers.
[0004] At present, there have been studies on the introduction of graphene into heterocyclic aramid fibers. For example, in Chinese invention patent CN113718364A, graphene is added to aramid resin as a graphene aramid spinning solution. However, the high viscosity aramid resin is directly mixed with graphene powder, which easily causes graphene to agglomerate, making the aramid composite fibers prepared by spinning uneven, unstable and poor in mechanical properties, making them difficult to use in actual production.
[0005] In addition, there are also some studies that introduce graphene quantum dots into polymer fibers, such as Chinese invention patent CN105543997A, which dissolves graphene quantum dots in a strong acid solution of para-aramid fiber (abbreviated as aramid II fiber) to prepare graphene quantum dot-modified aramid II fiber. Although the UV resistance of the fiber is improved, the strong acid damages the mechanical properties of the fiber.
[0006] Compared with the above-mentioned method of directly adding graphene powder or graphene quantum dot powder, pre-configuring a graphene dispersion can improve the dispersibility of graphene in the spinning solution to a certain extent, such as dissolving graphene in N, N dimethylacetamide / lithium chloride composite solvent in Chinese invention patent CN115216857A to obtain a dispersion of graphene, and then adding p-phenylenediamine, 2-(4-aminophenyl)-5-aminobenzimidazole, and terephthaloyl chloride monomer to the graphene dispersion to obtain a graphene aramid spinning solution. However, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole are directly dissolved in the dispersion of graphene oxide, which also has an adverse effect on the dispersibility of graphene. In addition, the lithium chloride in the composite solvent is easy to cause the graphene in the graphene dispersion to agglomerate due to the salt ion effect, so the graphene dispersion cannot be stored for a long time, and is only suitable for the preparation of the spinning solution immediately after the preparation is completed, which brings many inconveniences to the actual production.
[0007] Therefore, preparing a graphene quantum dot dispersion with simple process and uniform and stable properties, and achieving uniform distribution of graphene quantum dots in heterocyclic aramid fibers, are key factors in improving the mechanical properties of heterocyclic aramid fibers. Summary of the invention
[0008] In order to solve the above problems, the present invention discloses a method for preparing graphene quantum dot modified aramid III composite fiber and the aramid III composite fiber prepared by the method.
[0009] The present invention provides a method for preparing aramid III composite fibers, comprising: S1, dispersing amination-modified graphene quantum dots in N,N-dimethylacetamide solvent to form a dispersion; and S2, adding the dispersion into a polymerization reaction system before polymerization of aramid III monomers to form a composite spinning solution.
[0010] According to one embodiment, the mass percentage of nitrogen in the amination graphene quantum dots is greater than 0 and less than or equal to 30%.
[0011] According to another embodiment, the size of the amino graphene quantum dots is 1 nm-10 nm.
[0012] According to another embodiment, the content of the graphene quantum dots in the dispersion is less than or equal to 20 mg / ml.
[0013] According to another embodiment, the S2 step includes: dissolving lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in N,N-dimethylacetamide solvent to form a solution, adding the dispersion after the solution temperature is reduced to 10-15°C, stirring evenly, reducing the temperature to 5-10°C, adding terephthaloyl chloride, and reacting to obtain the composite spinning solution with a viscosity of 35,000 mPa·s to 80,000 mPa·s.
[0014] According to another embodiment, the time for adding the dispersion and stirring it evenly in step S2 is 5-20 minutes.
[0015] According to another embodiment, the preparation method further includes: S3, forming the aramid III composite fiber from the composite spinning solution by wet spinning.
[0016] According to another embodiment, the mass percentage of the amino graphene quantum dots in the aramid III composite fiber is 0.01-5%.
[0017] The present invention also provides an aramid III composite fiber prepared by the above preparation method.
[0018] The present invention directly dissolves graphene quantum dots with different degrees of amination in N,N-dimethylacetamide solvent without adding any cosolvents such as lithium chloride or calcium chloride. The graphene quantum dots are not easy to agglomerate in the solvent, are easy to store, and do not introduce any impurities. The graphene quantum dots have a size similar to that of the polymerization monomer 2-(4-aminophenyl)-5-aminobenzimidazole or p-phenylenediamine, and can be used as the "fourth monomer" of the polymerization reaction to participate in the generation of longer polymer molecular chains; since the amine content of the graphene quantum dots is controllable, the reaction activity is controllable, and the length of the polymer molecular chain is controllable, so that the mechanical properties of the fiber can be regulated, and then a fiber with high mechanical properties can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is the XPS spectrum of amino graphene quantum dot 1 and amino graphene quantum dot 2.
[0020] Figure 2 These are the Raman spectra of amino graphene quantum dots 1 and amino graphene quantum dots 2.
[0021] Figure 3 These are comparison photos of the dispersion of amino-modified graphene quantum dots 1 before and after storage. DETAILED DESCRIPTION
[0022] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions and drawings therein are essentially used for illustration rather than for limiting the present invention.
[0023] The preparation method of the aramid III composite fiber of the present invention comprises: S1, dispersing the amino graphene quantum dots in N, N-dimethylacetamide solvent to form a dispersion; and S2, adding the dispersion into the polymerization reaction system before the aramid III monomer is polymerized to form a composite spinning solution.
[0024] The "aramid III monomer" refers to the monomer that forms aramid III. "Before polymerization of aramid III monomer" means before the polymerization reaction occurs.
[0025] The method of the present invention dissolves the aminated graphene quantum dots in an N,N-dimethylacetamide solvent without adding any cosolvents such as lithium chloride or calcium chloride. Due to the excellent dispersibility of the graphene quantum dots, a uniformly dispersed dispersion can be obtained without adding any dispersant such as a surfactant, and the graphene quantum dots are not easy to agglomerate in the solvent and are easy to store. In addition, since there are no other additives and no impurities are introduced, the stability of the reaction system can be guaranteed, thereby improving the mechanical properties of the fiber.
[0026] In an optional embodiment, step S2 may be: dissolving lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole in N,N-dimethylacetamide solvent to form a solution, adding the dispersion after the solution temperature is reduced to 10-15°C, stirring evenly, reducing the temperature to 5-10°C, adding terephthaloyl chloride, and reacting to obtain a composite spinning solution with a viscosity of 35,000 mPa·s to 80,000 mPa·s. Among them, the lithium chloride cosolvent can be heat-treated before use to remove the moisture therein, for example, 400°C, muffle furnace heating for more than 3 hours. The process of dissolving lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole can be carried out under nitrogen protection. The time for adding the dispersion and stirring evenly can be 5-20 minutes to avoid the agglomeration of graphene quantum dots due to the long time of this period. The addition of terephthaloyl chloride can be batched, and those skilled in the art can determine the amount of each addition and the number of times of entry according to the reaction process.
[0027] In the method of the present invention, before the polymerization reaction occurs, the amination graphene quantum dot dispersion is added to a mixed solvent in which 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are completely dissolved in advance, and terephthaloyl chloride is added after stirring evenly (for example, stirring for 5-20 minutes). The advantage is that 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are mixed with the graphene quantum dot dispersion in the form of a solution, which can effectively avoid the graphene agglomeration caused by the addition of a high-viscosity polymerization solution of the graphene dispersion during or after the polymerization, and can also avoid the phenomenon of graphene agglomeration caused by the addition of solid graphene in the polymerization solution due to uneven dispersion. In the present invention, the graphene dispersion is added to the pre-dissolved 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine / N, N'-dimethylacetamide solution, which can reduce the stirring time of the graphene quantum dots in the reactor, and can make the graphene well dispersed in the composite solvent without agglomeration.
[0028] The aminated graphene quantum dots used in the present invention have a size similar to that of the polymerization monomer 2-(4-aminophenyl)-5-aminobenzimidazole or p-phenylenediamine, and have an amino group that can participate in the polymerization reaction, so they can be used as the "fourth monomer" of the polymerization reaction to participate in the generation of longer polymer molecular chains. Since the amino content of the graphene quantum dots is controllable, the reaction activity is controllable, and the length of the polymer molecular chain is controllable, so that the mechanical properties of the composite fiber can be regulated, and a composite fiber with high mechanical properties can be obtained. Due to the addition of graphene quantum dots, the composite fiber of the present invention can effectively enhance the interaction within the molecular chain and between the chains, enhance the mechanical properties of the composite fiber such as tensile strength, elongation at break, and Young's modulus, and has excellent corrosion resistance.
[0029] In an optional embodiment, the mass percentage of nitrogen in the aminated graphene quantum dots is greater than 0 and less than or equal to 30%. Since the amino content can control the reaction activity, thereby controlling the length of the polymer molecular chain and the mechanical properties of the fiber, those skilled in the art can select aminated graphene quantum dots with appropriate nitrogen content according to actual needs, such as but not limited to nitrogen content of 0.1%, 1.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, etc.
[0030] In an optional embodiment, the size of the amino graphene quantum dots is 1 nm-10 nm.
[0031] In an optional embodiment, the content of graphene quantum dots in the dispersion is less than or equal to 20 mg / ml to ensure that a dispersion with good dispersibility is obtained.
[0032] In an optional embodiment, the preparation method further includes: S3, forming aramid III composite fibers from the composite spinning solution by wet spinning.
[0033] In an optional embodiment, the mass percentage of the amination graphene quantum dots in the aramid III composite fiber is 0.01-5%. When the content of the amination graphene quantum dots exceeds 5%, the dispersibility of the amination graphene quantum dots in the polymer solution decreases, resulting in a decrease in the mechanical properties of the composite fiber. Therefore, the mass content of the amination graphene quantum dots in the composite fiber matrix is controlled to be 0.01-5%. For example, the content can be 0.01, 0.1%, 1%, 2%, 3%, 4%, 5%, etc.
[0034] The present invention is further described below by specific examples. However, these examples are merely exemplary and do not constitute any limitation to the scope of the present invention. In the following examples and comparative examples, the reagents, materials and instruments used are all commercially available unless otherwise specified.
[0035] Dispersion Preparation Examples 1-4
[0036] Aminated graphene quantum dots 1, 2, 3 and 4 were dissolved in N, N-dimethylacetamide solvent (the mass ratio of aminated graphene to N, N-dimethylacetamide was 0.24:1), and ultrasonically dispersed for 10 min using a cell disruptor 600W to prepare dispersions of aminated quantum dots 1 (hereinafter referred to as dispersion 1), aminated graphene quantum dots 2 (hereinafter referred to as dispersion 2), aminated quantum dots 3 dispersions (hereinafter referred to as dispersion 3) and aminated quantum dots 4 dispersions (hereinafter referred to as dispersion 4). The specific parameters of aminated graphene quantum dots 1-4 are shown in Table 1. Figure 1 The XPS spectra and Raman spectra of amino-modified graphene quantum dots 1-2 are shown. The nitrogen content and carbon-oxygen ratio are calculated from the XPS spectra, and the size of the quantum dots is determined from the transmission electron microscope (TEM) photos. D / I G Calculated from Raman spectroscopy. The calculation method for quantum dots 3 and 4 is the same as that for quantum dots 1-2, which is not shown in the figure. Figure 3 It shows that the dispersion of amino-modified graphene quantum dots 1 still has good dispersibility after being stored for 100 days.
[0037] Table 1 Structural characteristics of amino quantum dots
[0038]
[0039]
[0040] The following Examples 1-5 and Comparative Examples 1-3 respectively use the dispersions 1-4 prepared in Preparation Examples 1-4 to prepare aramid III composite fibers. The different dispersions and addition times used in Examples 1-5 and Comparative Examples 1-3 are specifically shown in Table 2.
[0041] Table 2
[0042]
[0043] Example 1
[0044] Weigh 600g of N,N-dimethylacetamide solvent and place it in a 1L glass jacketed reactor, and introduce nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 21g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 430ppm. Add 2.6524g of p-phenylenediamine and 12.8344g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, and the temperature of the solution in the reactor was lowered to 15°C. The quantum dot dispersion 1 was added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 16.1004g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, and the low-temperature thermostatic bath was removed. The reaction was stirred at a rate of 300 rpm for 40min. When the temperature rose to 21°C, 0.4150g of terephthaloyl chloride was added to the reactor. The reaction was continued to be stirred at a rate of 300 rpm for 30min. The reaction was terminated, and the viscosity of the polymer solution was measured to be 35,000 mPa·s.
[0045] The above composite spinning solution was prepared into composite fibers by wet spinning, and the spinning solution was poured into a degassing tank equipped with a metering pump and nitrogen. After vacuum defoaming treatment, the spinning solution was transported to the spinning tank on the spinning line. The spinning solution was extruded by a spinning pump and high-pressure nitrogen, transported to the spinneret, and passed through a three-stage coagulation bath, where a double diffusion process occurred. Primary fibers were obtained after washing and drying. Subsequently, graphene quantum dots / aramid III fibers were prepared by heating at 400°C for 2 min in a N2 atmosphere, and the fibers were collected by an automatic winding device. The mechanical properties of the fibers are shown in Table 3.
[0046] Example 2
[0047] Weigh 550g of N,N-dimethylacetamide solvent and place it in a 1L glass jacketed reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 19.25g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 390ppm. Add 2.4313g of p-phenylenediamine and 11.7649g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, and the temperature of the solution in the reactor was lowered to 15°C. The quantum dot dispersion 2 was added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 14.7587 g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, and the low-temperature thermostatic bath was removed. The reaction was stirred at a rate of 300 rpm for 36 min. When the temperature rose to 21°C, 0.3804 g of terephthaloyl chloride was added to the reactor. The reaction was continued to be stirred at a rate of 300 rpm for 35 min. The reaction was terminated, and the viscosity of the polymerization solution was measured to be 58,000 mPa·s.
[0048] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0049] Example 3
[0050] Weigh 600g of N,N-dimethylacetamide solvent and place it in a 1L glass jacketed reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 21g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min to fully dissolve lithium chloride. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 415ppm. Add 2.6524g of p-phenylenediamine and 12.8344g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min to fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, and the temperature of the solution in the reactor was lowered to 15°C. The quantum dot dispersion 2 was added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 16.1004g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, and the low-temperature thermostatic bath was removed. The reaction was stirred at a rate of 300 rpm for 42 minutes. When the temperature rose to 21°C, 0.4150g of terephthaloyl chloride was added to the reactor. The reaction was continued to be stirred at a rate of 300 rpm for 35 minutes. The reaction was terminated, and the viscosity of the polymer solution was measured to be 63,000 mPa·s.
[0051] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0052] Example 4
[0053] Weigh 500g of N,N-dimethylacetamide solvent and place it in a 1L glass jacketed reactor, and introduce nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 17.5g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 409ppm. Add 2.2103g of p-phenylenediamine and 10.6953g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, the temperature of the solution in the reactor was lowered to 15°C, and the quantum dot dispersion 4 was added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 13.417 g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, the low-temperature thermostatic bath was removed, and the reaction was stirred at a rate of 300 rpm for 45 min. When the temperature rose to 21°C, 0.3458 g of terephthaloyl chloride was added to the reactor, and the reaction was continued to be stirred at a rate of 300 rpm for 40 min. The reaction was terminated, and the viscosity of the polymerization solution was measured to be 56,000 mPa·s.
[0054] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0055] Example 5
[0056] Weigh 600g of N,N-dimethylacetamide solvent and place it in a 1L glass jacket reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 21g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 398ppm. Add 2.6524g of p-phenylenediamine and 12.8344g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, and the temperature of the solution in the reactor was lowered to 15°C. The quantum dot dispersion 3 was added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 16.1004 g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, the low-temperature thermostatic bath was removed, and the reaction was stirred at a rate of 300 rpm for 52 min. When the temperature rose to 21°C, 0.4150 g of terephthaloyl chloride was added to the reactor, and the reaction was continued to be stirred at a rate of 300 rpm for 40 min. The reaction was terminated, and the viscosity of the polymerization solution was measured to be 42,000 mPa·s.
[0057] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0058] Example 6
[0059] Weigh 500g of N,N-dimethylacetamide solvent and place it in a 1L glass jacket reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 17.5g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 420ppm. Add 2.2103g of p-phenylenediamine and 10.6953g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, and the temperature of the solution in the reactor was lowered to 15°C. The quantum dot dispersion 1 was added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 13.417 g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, the low-temperature thermostatic bath was removed, and the reaction was stirred at a rate of 300 rpm for 40 min. When the temperature rose to 21°C, 0.3458 g of terephthaloyl chloride was added to the reactor, and the reaction was continued to be stirred at a rate of 300 rpm for 35 min. The reaction was terminated, and the viscosity of the polymer solution was measured to be 54,000 mPa·s.
[0060] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0061] Comparative Example 1
[0062] Weigh 500g of N,N-dimethylacetamide solvent and place it in a 1L glass jacket reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 17.5g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 410ppm. Add 2.2103g of p-phenylenediamine and 10.6953g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, the temperature of the solution in the reactor was lowered to 10°C, and 13.4170 g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, the low-temperature thermostatic bath was removed, and the reaction was stirred at a rate of 300 rpm for 45 min. When the temperature rose to 21°C, 0.3458 g of terephthaloyl chloride was added to the reactor, and the reaction was continued to be stirred at a rate of 300 rpm for 35 min. The reaction was terminated, and the viscosity of the polymer solution was measured to be 47,000 mPa·s.
[0063] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0064] Comparative Example 2
[0065] Weigh 600g of N,N-dimethylacetamide solvent and place it in a 1L glass jacket reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 21g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 425ppm. Add 2.6524g of p-phenylenediamine and 12.8344g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, and the temperature of the solution in the reactor was lowered to 15°C. 24 mg of quantum dots 1 were added to the reactor. When the temperature of the solution in the reactor dropped to 10°C, 16.1004 g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, and the low-temperature thermostatic bath was removed. The reaction was stirred at a rate of 300 rpm for 48 min. When the temperature rose to 21°C, 0.4150 g of terephthaloyl chloride was added to the reactor. The reaction was continued to be stirred at a rate of 300 rpm for 40 min. The reaction was terminated, and the viscosity of the polymer solution was measured to be 53,000 mPa·s.
[0066] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0067] Comparative Example 3
[0068] Weigh 500g of N,N-dimethylacetamide solvent and place it in a 1L glass jacket reactor, and pass nitrogen into the reactor. Place lithium chloride in a muffle furnace and burn it at 400℃ for 4 hours to remove the moisture in lithium chloride. When the temperature in the furnace drops to about 200℃, weigh 17.5g of lithium chloride taken out of the muffle furnace and quickly transfer it to the reactor. Stir at a rate of 300 rpm for 30min, and the lithium chloride is fully dissolved. Add appropriate amount of water to the LiCl / DMAC solution to adjust the water content of the solution to 413ppm. Add 2.2103g of p-phenylenediamine and 10.6953g of 2-(4-aminophenyl)-5-aminobenzimidazole to the reactor, stir at a rate of 300 rpm for 30min, and fully dissolve. The polymerization kettle was connected to a low-temperature thermostatic bath, the temperature of the solution in the reactor was lowered to 10°C, and 13.417g of terephthaloyl chloride was added thereto. Since a large amount of heat was released by the reaction, the temperature of the solution in the polymerization kettle gradually increased. The temperature was continuously lowered until the temperature dropped to 10°C, the low-temperature thermostatic bath was removed, and the reaction was stirred at a rate of 300 rpm for 37min. When the temperature rose to 21°C, 0.3458g of terephthaloyl chloride was added to the reactor, and the reaction was continued at a rate of 300 rpm for 45min. The reaction was terminated, and the viscosity of the polymer solution was measured to be 72,000 mPa·s. The quantum dot dispersion 1 was added to the polymer solution and stirred for 1h to obtain a composite spinning solution.
[0069] The prepared composite spinning solution was subjected to wet spinning, and the spinning process was the same as that of Example 1. The mechanical properties of the fiber prepared in this example are shown in Table 3.
[0070] Table 3
[0071]
[0072]
[0073] By comparing the mechanical properties of Examples 1-5 and Comparative Example 1, it can be seen that the addition of amino-modified graphene quantum dots improves the mechanical properties of the aramid III fiber.
[0074] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing aramid III composite fiber, characterized in that: include: S1, dispersing the aminated graphene quantum dots in an N,N-dimethylacetamide solvent to form a dispersion; as well as S2, adding the dispersion into the polymerization reaction system before the polymerization of the aramid III monomer to form a composite spinning solution.
2. The preparation method according to claim 1, characterized in that: The mass percentage of nitrogen in the amino graphene quantum dots is greater than 0 and less than or equal to 30%.
3. The preparation method according to claim 1, characterized in that: The size of the amino graphene quantum dots is 1nm-10nm.
4. The preparation method according to claim 1, characterized in that: The content of the graphene quantum dots in the dispersion is less than or equal to 20 mg / ml.
5. The preparation method according to claim 1, characterized in that: The S2 step includes: Lithium chloride cosolvent, p-phenylenediamine and 2-(4-aminophenyl)-5-aminobenzimidazole are dissolved in N,N-dimethylacetamide solvent to form a solution, the solution temperature is reduced to 10-15°C and then the dispersion is added. After stirring evenly, the temperature is reduced to 5-10°C, terephthaloyl chloride is added, and the composite spinning solution with a viscosity of 35,000 mPa·s to 80,000 mPa·s is obtained by reaction.
6. The preparation method according to claim 1, characterized in that: The time for adding the dispersion and stirring it evenly in step S2 is 5-20 minutes.
7. The preparation method according to claim 1, characterized in that: The preparation method further comprises: S3, forming the aramid III composite fiber by wet spinning the composite spinning solution.
8. The preparation method according to claim 1, characterized in that: The mass percentage of the amino graphene quantum dots in the aramid III composite fiber is 0.01-5%.
9. An aramid III composite fiber, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
UV-resistant graphene quantum dot composite p-aramid fiber preparation method
CN105543997A
Graphene high-strength impact-resistant aramid fiber and preparation method thereof
CN113718364A
Preparation method of graphene modified high-strength and high-modulus heterocyclic aramid
CN115216857A
Preparation method of graphene quantum dot enhanced p-aramid fiber
CN105442076A
Graphene dispersion liquid and preparation method thereof
CN111232966A